Between Sympathy, Fascination, and Powerlessness. The Experiences of Health Professionals During the Medical Monitoring of a Hunger Strike Among Undocumented Migrants - Rita Vanobberghen; Dirk Lafaut; Fred Louckx; Dirk Devroey; Jan Vandevoorde (Frontiers Media S.A., 2022)
In 2014, a group of undocumented migrants started a hunger strike in Brussels. The medical monitoring was mainly done by young, committed health professionals with no prior experience of medical monitoring of people on hunger strike. Following the hunger strike, two focus groups were organized to assess the experiences of the health professionals during the medical monitoring of the hunger strike. Their main motivation for assisting was wanting to help the people on hunger strike but they were also curious about the living conditions among undocumented migrants and the reasons behind starting the strike. They were puzzled by the paradox of hunger strikers putting their life at risk in order to get a better life and obtain a residence permit. They felt conflicted about their own role as a caregiver: they did not know how to deal with patients who did not comply with medical advice, they struggled to build a relationship of mutual trust and feared that they would end up being instrumentalized by the hunger strikers or their environment. Afterwards, some of the health professionals were deeply touched by the experience and there were reports of symptoms of secondary traumatic stress such as re-experiencing and avoidance. During the focus group's discussions, the respondents made suggestions on how to improve the medical monitoring in the event of any future hunger strikes.